Multi-start metaheuristic for transmission system expansion planning using a transportation model - Da Silva, Silvia Mara Lima [UNESP]; Romero, Ruben [UNESP]; De Faria, Lucas Teles [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
This work presents a multi-start metaheuristic for transmission system expansion planning. The transmission network is modelled as a transportation network. The method progresses in two stages: constructive phase and local search phase. In construction phase, the diversification is carried out where the search space is explored to obtain feasible solutions of good quality. In local search phase, the intensification is carried out. It is based on the intensive search in the vicinity of feasible solutions found in the construction phase. The test systems of Garver six-bus network, IEEE 24-bus network and Southern 46-bus network were represented using the transport model. The results demonstrate the efficiency of the adopted strategy. All the optimal solutions of the aforementioned test systems were found with a reduced number of linear programming problems solved and also with reduced computational time.
Keywords: Combinatorial Optimization; Multi-Start Metaheuristic; Transmission System Expansion Planning; Transportation Model